The Influence of Individual Personality Factors, Locus of Control and Self Efficacy on the Performance of SME’s in the Food Industry Sector - Titania Ayu Rizqia; Rochiyati Murniningsih; Dahli Suhaeli; Eni Zuhriyah (Urecol Journal. Part G: Multidisciplinary Research, 2022)
This study aims to examine whether individual personality, locus of control, and self-effecacy affect the performance of micro, small and medium enterprises in the food industry sector in Magelang City. This research method uses descriptive quantitative. Data processing was tested using multiple linear regression test. The sampling technique used purposive sampling with a total of 88 respondents. The results of this study indicate that individual personality, locus of control, and self-effecacy simultaneously have a positive effect on micro, small and medium enterprises, individual personality partially has a positive effect on micro, small, and medium enterprises, locus of control partially has no effect on micro, small, and medium enterprises, and self-effecacy partially has poritive effect on mocro, small, and medium enterprises.